2014
DOI: 10.1007/s10734-014-9844-8
|View full text |Cite
|
Sign up to set email alerts
|

Age differences explain social class differences in students’ friendship at university: implications for transition and retention

Abstract: The present research tested the hypotheses that (a) working-class students have fewer friends at university than middle-class students, and (b) this social class difference occurs because working-class students tend to be older than middle-class students. A sample of 376 first-year undergraduate students from an Australian university completed an online survey that contained measures of social class and age as well as quality and quantity of actual and desired friendship at university. Consistent with predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Our qualitative data suggested that timing of social events around commutes, as well as start times of lectures and availability of suitable space on campus, were all important to students. This is in broad agreement with what others have found (Thomas & Jones, 2017), and is not unique to this institution; the difficulties for traditionally atypical students have been recognised in the literature (Read et al, 2018;Pokorny et al, 2017;Carruthers Thomas, 2016;Rubin & Wright, 2015;Read et al, 2003).…”
Section: 'Being a Commuting Student Not Around As Much'supporting
confidence: 91%
See 2 more Smart Citations
“…Our qualitative data suggested that timing of social events around commutes, as well as start times of lectures and availability of suitable space on campus, were all important to students. This is in broad agreement with what others have found (Thomas & Jones, 2017), and is not unique to this institution; the difficulties for traditionally atypical students have been recognised in the literature (Read et al, 2018;Pokorny et al, 2017;Carruthers Thomas, 2016;Rubin & Wright, 2015;Read et al, 2003).…”
Section: 'Being a Commuting Student Not Around As Much'supporting
confidence: 91%
“…Perhaps in the case of students this may be imagined as gaining mastery of a subject or establishing a secure learner identity. An intrinsic part of belonging is that it is by its very nature exclusive, since not everyone will belong (Rubin & Wright, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since low-SES students are usually older than high-SES students, they often have to work off campus and to take care of their family (Terenzini, Springer, Yaeger, Pascarella, & Nora, 1996). Consequently, they have less time to devote to the college community and have fewer friends (Terenzini et al, 1996), which ultimately impairs their social integration (Rubin & Wright, 2015, 2017). In addition, a recent line of research has shown that due to low familiarity with the cultural codes of higher education emphasizing independence, low-SES students also have fewer personal resources (i.e., they have a more interdependently shaped self-construal) to meet the expectation of this environment than higher SES students (Stephens, Hamedani, & Destin, 2014).…”
Section: Students’ Ses and Sense Of Belongingmentioning
confidence: 99%
“…Curtin, 2011;Rubin & Wright, 2015;Soria, Stebleton, & Huesman, 2013;Wiederkher, Bonnot, Krauth-Gruber, & Darnon, 2015). As Keefer, Goode, and Berkel (2015) found the relevance of the class consciousness in the social and political psychology literature, it is shown that the current use of subjective measure misses some important picture about social class.…”
mentioning
confidence: 99%